Decomposition And Insect Succession Pattern On Monkey Carcasses Placed Indoor And Outdoor With Notes On The Life Table Of Chrysomya Rufifacies (Diptera: Calliphoridae) - Sundharavalli, Ramayah (2014)

(untitled)
This study was conducted in the Durian Valley, USM, Penang from 15 February to 4 April, 11 June to 30 July and 10 October to 28 November, 2012, using total of 18 monkey carcasses; 6 carcasses per study period. Kajian ini dijalankan di Lembah Durian, USM, Pulau Pinang dari 15 Februari hingga 4 April, 11 Jun hingga 30 Julai dan 10 Oktober hingga 28 November, 2012, dengan menggunakan 18 bangkai monyet; 6 bangkai monyet bagi setiap tempoh kajian.